Optimization of temperature measurement on the bus drum brake as a basis for developing brake fault signals - Siregar, Rolan; Adhitya, Mohammad; Sumarsono, Danardono A; Nazaruddin, Nazaruddin; Heryana, Ghany; Prasetya, Sonki; Zainuri, Fuad (Eastern-European Journal of Enterprise Technologies, 2021)
Brake failure is always possible due to several factors that are difficult to control, such as a slight leak in the brake hose due to an impact or a rat bite. In the latest research, the development of a brake performance detection tool has been started, but how to detect a brake temperature more efficiently on the brakes of large vehicles has not been specified. Given the significant impact of losses due to brake failure and accidents that are still occurring, this research plays an important role. It must be completed immediately so that accident cases can be reduced. The object of this research is where the position of the maximum brake temperature occurs? How to measure brake temperature is more practical? What sensor is optimal in detecting a brake temperature? The research method is carried out in a systematic stage that ends with an experimental method. This study indicates that the maximum temperature is relative to the entire friction area between the canvas and the drum brake. The most efficient sensor placement is in the hole in the drum brake cover so that installation is more practical and the brakes are not disturbed by the sensor’s presence. The optimal sensor is a thermocouple sensor because it is more stable to vibrations and more resistant to mud disturbances than infrared sensors. When using a thermocouple sensor, the temperature detection results must be corrected. The correction factor can be made with the equation y=10.3670+1.3205x–0.0003x2, where y is the actual temperature displayed, and x is the input temperature from the thermocouple sensor’s initial detection. Accurate brake temperature detection results will be developed as a signal for detecting brake faults in real-time to avoid brake failure. Finally, the safety of public transportation can be improved